Approach to synthesis of prednisolone from 9α-hydroxy androstenedione - Huy, Luu Duc; Diep, Nguyen Thi; Chang-Hee, Lee; Hung, Nguyen Duc (Vietnam Journal of Chemistry, 2014)
In this report we showed an efficient approach to synthesis of prednisolone from 9α-hydroxy androst-4-ene-3,17-dione via 16α,17α-epoxy-pregn-4,9(11)-diene-21-ol-3,20-dione. Structure of obtained products has been studied by spectral methods such as IR, MS, NMR. Keywords: 9α-hydroxy androst-4-ene-3,17-dione,16α,17α-epoxy- pregn-4,9(11)-diene-21-ol-3,20-dione.